(untitled) (CIPEEX, 2025)
Introduction: Since the internet became an integral part of daily human life in the early 2000s, the use of social networks has grown continuously, to the point of becoming addictive, mainly among adolescents. Objective: Therefore, the present study seeks to examine how excessive engagement with the internet may influence anxiety and depression symptoms within this age group. Methodology: This study constitutes an integrative literature review. After conducting searches in the National Library of Medicine (PubMed) and Google Scholar databases and subsequently applying the established eligibility and exclusion criteria, six articles were included in the present review. Results: Findings suggest that internet addiction (IA) in adolescents has been associated with structural and functional brain modifications and, consequently, with a higher prevalence and greater severity of depressive and anxiety symptoms. Conclusion: Thus, social media dependence is strongly associated with the worsening of depression and anxiety, becoming an integral component of a vicious cycle that undermines psychosocial well-being and neurological development in this age group, who are particularly vulnerable due to heightened brain plasticity.